Uncovering pyrethroid resistance mechanisms in Anopheles punctulatus group mosquitoes: A novel insight from Keerom, Papua, Indonesia - Lepa Syahrani; Puji B. S. Asih; Ismail E. Rozi; Astari Dwiranti; Dendi H. Permana; Irdayanti Irdayanti; Anom Bowolaksono; Din Syafruddin (International Journal of One Health)
Background and Aim: Malaria control programs in Indonesia heavily rely on insecticide-based interventions such as long-lasting insecticidal nets (LLINs) and indoor residual spraying (IRS). However, the effectiveness of these strategies is increasingly compromised by the emergence of insecticide resistance, particularly in high-transmission regions like Papua Province. The mechanisms underlying pyrethroid resistance in local vector populations remain inadequately characterized. This study aimed to assess the permethrin resistance status and characterize the frequency of L1014F/S knockdown resistance (kdr) alleles in Anopheles punctulatus group mosquitoes in Keerom, Papua, to inform region-specific malaria vector control strategies.